The Epidemiology of Ground Glass Opacity Lung Adenocarcinoma: A Network-Based Cumulative Meta-Analysis - Li, Xiongfei; Ren, Fan; Wang, Shuhang; He, Zhicheng; Song, Zuoqing; Chen, Jun; Xu, Song (Frontiers in Oncology, 2020)
Introduction: Due to the introduction of low-dose computed tomography (CT) and screening procedures, the proportion of early stage lung cancer with ground glass opacity (GGO) manifestation is increasing in clinical practice. However, its epidemiological characteristics is still not fully investigated. Methods: We retrieved all solitary GGO adenocarcinoma lung cancer (ADLC) on the PubMed, Cochrane Library and Embase databases until Jan 1, 2019 and extracted the general information to perform the meta-analysis, mainly focusing on age, gender and smoking status. Results: A total of 8793 solitary GGO ADLC patients from 53 studies were included in this analysis. The final pooled analysis showed that the female proportion, average diagnosis age and nonsmoking proportion of solitary GGO ADLC was 0.62 (95% CI: 0.60-0.64), 56.97 (CI95% 54.56-59.37) and 0.72 (CI95% 0.66-0.77), respectively. The cumulative meta-analysis and meta-trend analysis confirmed that the average age at diagnosis has been decreasing while the nonsmoking proportion significantly increased in the past two decades. Conclusions: From our epidemiological analysis, it demonstrates that the clinical characteristics of GGO lung cancer patients may be out of the high risk factors. Therefore, we propose to reconsider the risk assessment and current lung cancer screening criteria.